PBN (Phenyl-N-Tert-Butylnitrone)-Derivatives Are Effective in Slowing the Visual Cycle and Rhodopsin Regeneration and in Protecting the Retina from Light-Induced Damage. - Megan Stiles; Gennadiy P Moiseyev; Madeline L Budda; Annette Linens; Richard S Brush; Hui Qi; Gary L White; Roman F Wolf; Jian-Xing Ma; Robert Floyd; Robert E Anderson; Nawajes A Mandal (PLoS ONE)
A2E and related toxic molecules are part of lipofuscin found in the retinal pigment epithelial (RPE) cells in eyes affected by Stargardt's disease, age-related macular degeneration (AMD), and other retinal degenerations. A novel therapeutic approach for treating such degenerations involves slowing down the visual cycle, which could reduce the amount of A2E in the RPE. This can be accomplished by inhibiting RPE65, which produces 11-cis-retinol from all-trans-retinyl esters. We recently showed that phenyl-N-tert-butylnitrone (PBN) inhibits RPE65 enzyme activity in RPE cells. In this study we show that like PBN, certain PBN-derivatives (PBNDs) such as 4-F-PBN, 4-CF3-PBN, 3,4-di-F-PBN, and 4-CH3-PBN can inhibit RPE65 and synthesis of 11-cis-retinol in in vitro assays using bovine RPE microsomes. We further demonstrate that systemic (intraperitoneal, IP) administration of these PBNDs protect the rat retina from light damage. Electroretinography (ERG) and histological analysis showed that rats treated with PBNDs retained ~90% of their photoreceptor cells compared to a complete loss of function and 90% loss of photoreceptors in the central retina in rats treated with vehicle/control injections. Topically applied PBN and PBNDs also significantly slowed the rate of the visual cycle in mouse and baboon eyes. One hour dark adaptation resulted in 75-80% recovery of bleachable rhodopsin in control/vehicle treated mice. Eye drops of 5% 4-CH3-PBN were most effective, inhibiting the regeneration of bleachable rhodopsin significantly (60% compared to vehicle control). In addition, a 10% concentration of PBN and 5% concentration of 4-CH3-PBN in baboon eyes inhibited the visual cycle by 60% and by 30%, respectively. We have identified a group of PBN related nitrones that can reach the target tissue (RPE) by systemic and topical application and slow the rate of rhodopsin regeneration and therefore the visual cycle in mouse and baboon eyes. PBNDs can also protect the rat retina from light damage. There is potential in developing these compounds as preventative therapeutics for the treatment of human retinal degenerations in which the accumulation of lipofuscin may be pathogenic.